-6y+4=-4(2y+2)

Apply the distributive property.

-6y+4=-4(2y)-4⋅2

Multiply.

Multiply 2 by -4.

-6y+4=-8y-4⋅2

Multiply -4 by 2.

-6y+4=-8y-8

-6y+4=-8y-8

-6y+4=-8y-8

Add 8y to both sides of the equation.

-6y+4+8y=-8

Add -6y and 8y.

2y+4=-8

2y+4=-8

Subtract 4 from both sides of the equation.

2y=-8-4

Subtract 4 from -8.

2y=-12

2y=-12

Divide each term in 2y=-12 by 2.

2y2=-122

Cancel the common factor of 2.

Cancel the common factor.

2y2=-122

Divide y by 1.

y=-122

y=-122

Divide -12 by 2.

y=-6

y=-6

Solve for y -6y+4=-4(2y+2)